2018
DOI: 10.1177/1470785318819979
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the helpfulness of online customer reviews: The role of title features

Abstract: Nowadays, many people refer to online customer reviews that are available on most shopping websites to make a better purchase decision. An automated review helpfulness prediction model can help the websites to rank reviews based on their level of helpfulness. This study examines the effect of review title features on predicting the helpfulness of online reviews. Moreover, a new method is proposed to categorize action verbs in a review text. Text, reviewer, readability, and title features are the four main cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…The length of review and the review rating were identified as key features [50]. Moreover, it has been stated that the title features did not have a significant effect on the usefulness of the review [51].…”
Section: B Features For Predicting Review Helpfulnessmentioning
confidence: 99%
See 3 more Smart Citations
“…The length of review and the review rating were identified as key features [50]. Moreover, it has been stated that the title features did not have a significant effect on the usefulness of the review [51].…”
Section: B Features For Predicting Review Helpfulnessmentioning
confidence: 99%
“…The reviewer popularity and experience feature, i.e. number of compliments [52], number of friends [52], number of fans [52], number of reviews [38], [50]- [53], [68], [77], useful votes [38], [50]- [53], [75], [80], average useful votes [53], [77], credibility [39], [50], [51], [54], [78], recency [50], [53], frequency [50], [53], monetary [50], [53] and country [51] has been listed in literature. Whereas very few studies have attempted to explore the relationship between the reviewer's rating behavior and helpfulness of their reviews [29], [63].…”
Section: B Features For Predicting Review Helpfulnessmentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed model was tested on a collected dataset of book reviews using ML algorithms i.e., Decision Tree (DT) and RandF. It was reported that the review title features were not a significant predictor of review helpfulness [42]. A model based on GB algorithm was proposed to predict review helpfulness by using textual features of reviews, i.e., readability, polarity, and subjectivity.…”
Section: Literature Reviewmentioning
confidence: 99%